Decreased levels of stem cell factor in subjects with incident coronary events. (14th October 2015) - Wigren, M.; Rattik, S.; Hultman, K.; Björkbacka, H.; Nordin‐Fredrikson, G.; Bengtsson, E.; Hedblad, B.; Siegbahn, A.; Gonçalves, I.; Nilsson, J.
Abstract: Background: It has been proposed that vascular progenitor cells play an important role in vascular repair, but their possible clinical importance in cardiovascular disease has not been fully characterized. Vascular endothelial growth factor A, placental growth factor and stem cell factor (SCF) are three growth factors that are important in recruiting vascular progenitor cells. In this study, we investigated the association between the plasma levels of these growth factors and incident coronary events (CEs). Methods: Levels of the three growth factors were measured using the proximity extension assay technique in baseline plasma samples from 384 subjects with a first CE (mean follow‐up 14.0 ± 4.3 years) and 409 event‐free control subjects matched by sex and age, as well as in homogenates from 201 endarterectomy specimens. Results: After controlling for known cardiovascular disease risk factors in a Cox regression model, subjects in the lowest SCF tertile had a hazard ratio of 1.70 (95% confidence interval 1.14–2.54) compared with subjects in the highest SCF tertile. Lower SCF levels were also associated with more severe carotid disease, less fibrous atherosclerotic plaques and an increased incidence of heart failure. Expression of the SCF receptor c‐kit was demonstrated in the subendothelial layer and fibrous cap of human atherosclerotic plaques. Smokers and subjects with diabetes had decreased levels of SCF compared with control subjects. Conclusion: To our knowledge, this is the first clinical study to provide evidence to support a key role for SCF and progenitor cells in vascular repair. We suggest that the SCF–c‐kit pathway may be a promising biomarker and therapeutic target in cardiovascular disease.